THE PROCESS OF INDONESIAN NATION STATE FORMATION, 1901-1998 - Nasution Nasution (Paramita: Historical Studies Journal)
This article has analyzed the long process of Indonesian Nation State Formation, namely from the Dutch Colonial Period to New Order Era of the 1980s and 1990s. The article argues that the concept of nationhood remained very fluid for long time but gradually it started to shape after the introduction of western education to the natives in the Dutch Colonial era and it took the final shape in New Order Era. The complexity of the nation-state formation was due to the region consists of many ethnics, cultures, languages, religions, and political parties. Their national identity started from the ethnicity awareness which took shape in the Dutch Colonial Era. During the Japanese occupation era the Nation State Formation of Indonesia was put into action as Kurasawa said that they had been prepared the independence of Indonesian nation. In Sukarno era, Indonesia was still ideologically divided into some international ideologies such as Communism, Islamism, and the secular national ideology. The peak of the rivals is the breaking of Indonesian Communist Party uprising in 1965. A major change took place with the fall of Sukarno’s regime which was replaced by General Suharto. Suharto called the Sukarno era as the old order regime and called his regime as New Order. The stability of Indonesian National formation was restored with ban on the International Ideology such as Communism, forcing the Moslem militancy and using National Ideology (Pancasila) as the ones of National Ideology.